DYNAMICS OF ENGLISH LEARNING: A CASE STUDY ON MKUE-CONTEXTUAL DIALOGICAL LITERACY BASED LEARNING IN S2 BE FKIP UNTAN - Sutapa. Y, Y. Gatot (Jurnal Pembelajaran Prospektif, 2018)
This research was to describe the dynamic implementation of KKNI-Based Curriculum through contextual dialogical literacy. The findings revealed that General Skilled English Subjects (MKUE) in the concept of pragmatism integrates the understanding of current applicative and exploratory competence. With purposive sampling, 24 S2 BE students predominantly stated that MKUE learning based on contextual dialogical literacy accelerated mastery comprehensively in receptive and productive communication. MKUE accommodates the performance of contextual dialogue emphasizing the context of reading, sharing, and reflecting. Materials development, presentation management, question answering, and packaging arguments encourage S2 BE students to appear as innovative learners. The aspect of competition did not arise for its winning nature. Collaborative and co-learning aspects dominate as a social reflection of the spirit of dialogue and cooperation. Whereas, current intensity is in demand as an application of the practical concept of the digital era in integrating technological progress into MKUE, through descriptive exploration, the data concluded that students are facilitated to develop their competence dynamically, integratedly, and innovatively presented in MKUE learning. They are advised to implement this approach maximally, especially in integrating the development of learning materials with local content insights.